Rheological evaluation of industrial tomato in raw and processed condition - Tóth, A. R.; Tóthné Bogárdi, A.; Rubóczki, T.; Takácsné Hájos, M. (International Journal of Horticultural Science, 2020)
Tomato (Lycopersicon esculentum Mill.) is the second most important vegetable with one of the biggest producing areas worldwide, and an increasing tendency in Hungary as well. To fulfil the growing demands of the industry the producers must use the most suitable genotypes for the given conditions. In the experiment six genotypes (‘Heinz 1015 F1‘,‘Heinz 9478 F1‘,‘Kecskeméti 407‘,‘NUN254 F1‘,‘Prestomech F1‘ and ‘Rustico F1‘) were evaluated for different quality parameters: fruit shape index (length/diameter), firmness (g cm-2), force needed to tear the skin (kg-1) and consistency of tomato puree (g*sec). According to the results, the ‘Heinz 1015 F1‘ and ‘Heinz 9478 F1‘ were the most suitable genotypes for industrial processing in the mean of fruit quality. Strong positive correlation between consistency of juice and fruit shape index (r=0.891) and firmness of berry (r=0.882) was confirmed. The results have proved the necessity of these quality parameter measurements, which are important for the evaluation of raw material.